Why Don't Languages Adapt to Their Environment? - Mendívil-Giró, José-Luis (Frontiers in Communication, 2018)
The issue of whether languages adapt to their environment depends on our understanding of language, adaptation and environment. I consider these three concepts from an internalist or biolinguistic point of view. If adaptation is defined as the result of the differential transmission of phenotypic traits by means of natural selection, then both natural species and languages are adapted. Recall that according to Darwin’s own insight, the evolutionary mechanisms for species and languages are “curiously the same” (or “curiously parallel”). However, if the concept of adaptation entails that the environment is the essential source of the structure of evolving objects, then neither natural species nor languages can be said to be adapted to their environment. In the case of languages, I will argue that much of their structure is insensitive to historical change and, therefore, incapable of adaptation to the external environment. The immediate environment of languages is in fact internal to the mind/brain and is thus less variable than the social and physical environment in which people live. On the other hand, the dimensions of languages that are variable have such an indirect relation with the physical and social environment that the notion of adaptation to extra-linguistic reality can only be applied weakly, and then it is unable to explain the main patterns of linguistic structural diversity.